Unveiling the palate: exploring compositional perceptual mapping to analyze dietary preferences across food groups - Roy, Surjya Kanta; Satyapriya,; Burman, Rajarshi Roy; Bishnoi, Sitaram; Lenin, Venu; Sahu, Subhashree; Mahra, Girijesh Singh; Singh, Rahul; Joshi, Pratibha; Wason, Monika; Barua, Sukanya; Kademani, Sujay B. (Frontiers in Sustainable Food Systems, 2025)
IntroductionIndia’s food production and utilization status have affected the health and wellbeing of the population and healthcare systems. As a result, women, adolescent girls, and children are suffering anaemia which causes delayed mental and psychomotor development, morbidity, and maternal mortality. Several programs are running i.e. Public Distribution System (PDS), Integrated Child Development Scheme (ICDS) and Mid-Day Meal (MDM) etc. while targeting the vulnerable communities of India to meet their basic food and nutrition requirements.MethodsThe study was conducted in the Bundelkhand region, a nutritionally vulnerable area with a high infant mortality rate and an average Human Development Index score below the national average. A total of 320 respondents from four districts were selected for the study, and are being asked about their preferences of food groups in four meals.ResultsResults showed respondents have a discernible preference for certain foods across the four meals. The most well-liked food groups were “Oil/fat”, “Cereals”, “Roots/tubers” and “Vegetables”. They preferred more food groups to be included in dinner followed by lunch. The study found a strong correlation between the food groups “Cereals”, “Roots/tubers” and “Oil/fat” and the three primary meals of the day, namely breakfast, lunch, and dinner. Fish and meat are preferred during evening meals, serving as a valuable protein source.DiscussionThis trend in food habits is influenced by the cereal-based production systems, cultural norms and social dynamics of India, which needs a major reform.